Morphometric Analysis of Hard Palate on Nepalese Population - Khatiwada, Sushma; Chaulagain, Rajib; Khan, Gulam Anwer; Sapkota, Srijana Mishra; Adhikari Sudhin, Budhi Nath (Journal of Karnali Academy of Health Sciences, 2020)
Background: The hard palate is an important part of the human skull located between the nasal and the oral cavity. Hard palate plays an important role in the production of speech. The present study aimed to measure the morphometry of the hard palate and explore the existence of gender related differences since limited similar studies has been carried out. Methods: This study was conducted to assess the palatal dimensions in a sample of Nepalese individuals aged 18–25 years with class I molar occlusion. The data collection was done from January 2020 to March 2020. The length, breadth and height of the hard palate were measured and palatine indices as well as palatal height indices were calculated. Differences between males and females were tested for the palatal variables. Results: Mean palatal length, breadth and width were 41.58 ± 3.48 mm, 40.63 ± 3.76 mm, and 14.90 ± 2.04 mm respectively. We found significant gender difference in palatal morphometry in the cast we analyzed. The palatine index of majority of dental cast was of brachystaphyline type (84.85%). Calculation of the palatine height index demonstrated predominance of orthostaphyline type (71.21%) of dental casts. Conclusion: The present study provides important palatal morphological data of the Nepalese population which can be helpful for orthodontic treatment as well as for anthropological studies, greater palatine nerve blocks and surgical procedures on the hard palate.